Protective Effects and Potential Mechanisms of Dietary Resveratrol Supplementation on the Spleen of Broilers Under Heat Stress - Meng, Tiantian; Deng, Juying; Xiao, Dingfu; Arowolo, Muhammed Adebayo; Liu, Chunming; Chen, Liang; Deng, Wei; He, Shaoping; He, Jianhua (Frontiers in Nutrition, 2022)
Resveratrol (RSV) is a natural polyphenolic compound with potent antioxidant and anti-inflammatory properties. This study aimed to investigate the protective effects of RSV supplementation on the inflammatory responses of broilers during heat stress. A total of 432 28-d-old white-feathered broilers (817 crossbred chicken) with an average weight of 549 ± 4g were randomly allotted to 4 equal groups (Half male and half female, 6 replicates/group, 18 chickens/replicate), including normal temperature (NT) group (24 ± 2°C for 24 h/d, basal diet), NT+RSV group (24 ± 2°C for 24 h/d, basal diet + RSV), heat stress (HT) group (37 ± 2℃ for 8 h/d, basal diet), and HT+RSV group (37 ± 2℃ for 8 h/d, basal diet + RSV). Serum samples were collected on d 7 and 14 of heat stress, and thymus, spleen, jejunum, and bursa of Fabricius samples were collected and analyzed on d14. RSV treatment decreased the feed conversion ratio, partially reversed the negative alternations in body weight, average daily gain, and average daily feed intake caused by heat stress. RSV treatment also decreased the elevated levels of corticosterone on d 14, adrenocorticotropic hormone, and triiodothyronine in serum on d 7 caused by heat stress, and significantly increased the villus height to crypt depth ratio in the jejunum on d 14. Dietary RSV also reduced heat stress-induced splenic pro-inflammatory cytokine concentrations. TUNEL assay showed that RSV significantly reduced heat stress-induced the number of apoptotic cells. Remarkably, RSV down-regulated some splenic related genes for apoptosis genes, including BCL-2, Apaf-1, and MDM2 mRNA levels induced by heat stress. According to GO and KEGG enrichment analyses, the differential genes between HT and HT+RSV groups were mainly associated with immune system process, hematopoietic or lymphoid organ development, and toll-like receptor signaling pathway. The relative mRNA expression of NF-κB, heat shock protein 70 (HSP70), and p38 MAPK were markedly decreased by the combination of RSV and heat stress. These findings showed that RSV might reduce the splenic inflammatory response in heat-stressed white-feather broilers by inhibiting heat stress-induced activation of NF-B, MAPK, and HSP70, as well as inhibiting the activation of mitochondrial apoptotic pathways.